Alteraciones neuropsicológicas en escolares de un municipio con niveles elevados de vapor de mercurio medioambiental, Colombia, 2008-2009 (2011)
ABSTRACT: To establish the prevalence of neuropsychological disorders in the language, memory, executive functions, and attention of schoolchildren studying from second grade of elementary school to ninth grade of high school in the Segovia municipality. As a result of the artisanal mining of gold, this region shows environmental concentrations of mercury vapor that exceed the prescribed exposure limits. Methodology: the Rey complex figure test, the phonological and semantic test (FAS), the associated pairs test, the token test, the Stroop test, and the digits subtest were all applied as part of the protocol for assessing these functions. Results: 79.6% of schoolchildren in Segovia presented alteration in language comprehension; 77.6% in executive functioning; 52.6% in visual attention; 43.9% in verbal fluency; 38.8% in short-term verbal memory, and 31.1% in long-term verbal memory. Conclusion: the prevalence of these anomalies among schoolchildren in Segovia are alarming, therefore a psychosocial intervention is needed to respond effectively to such a problematic scenario.